Edukasi dan Pembentukan Kader Covid19 Tingkat Rukun Tetangga (RT) - Ruli Bahyu Antika; eri witcahyo; Anita Dewi Moelyaningrum (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Pandemic covid19 should be handled together between government and community. The government programs will not be optimal without supporting the community. The problems were the gap in information and education about covid19, especially how to prevent the covid19, vaccine, health protocols, and how to make and use eco hand sanitizer. The aim of the community service was to give the education and covid19 cadres of the neighborhood association. The method of the community service was education intervention, counseling, and training about covid19, vaccine, health protocols (mask using, physical distancing, washing the hands, social distancing, reducing mobility), and making and using the eco hand sanitizer. Pre-test and post-test were conducted to evaluate these community service programs. The result showed that there was an increase in knowledge about the covid19, vaccine 25,6%; implemented the health protocols (19,1%). The media that using for education, counseling, and training were acceptable (65,2%). The community, especially cadres were active in joint the whole activity such as the installation of educational banners in various locations and corners of the village, as well as in the distribution of masks and the manufacture of hand sanitizer. The obstacle in this activity is adjusting the training time for cadres and the community because they still have to work.